Devoted to nature : the religious roots of American environmentalism - Berry, Evan, 1977- (University of California Press, 2015)
"Devoted to Nature explores the religious underpinnings of American environmentalism, tracing the theological character of American environment thought from their Romantic foundations to contemporary discourse about nature spirituality. This history is most readily visible during the Gilded Age and Progressive Era, when religious sources tangibly shaped ideas about the natural world, recreational practices, and modes of social and political interaction. The roots of the environmental movement evidence explicitly Christian understandings of salvation, redemption, and progress, which provided the context for Americans enthusiastic about the out-of-doors and established the horizons of possibility for the national environmental imagination"--Provided by publisher.